Liberal arts and sciences graduates’ reflections on their cooperative education experiences and career self-efficacy - Brantley, Jennifer (Kansas State University, 2012)
The purpose of this phenomenological study was to provide insight into Liberal Arts and Sciences (LAS) graduates’ reflections on their cooperative education (co-op) experiences and resulting career self-efficacy. Wichita State University houses a cooperative education program, the only one of its kind in the state of Kansas. This program helps students in all academic disciplines find work experiences related to their major for which they can earn academic credit, and sometimes even get paid. Engineering and business students typically identify immediate benefits of participating in cooperative education; however, LAS administrators, faculty, and students have been slower to accept and include this experience in their academic programs. The two research questions that guided this study were: (a) How do former LAS students describe their co-op experience? and (b) What did these students gain, with regard to career self-efficacy, through their co-op experience? Because LAS students may not learn skills specifically related to a career due to the general nature of an LAS degree program, the current study focuses more on the graduates’ reflections of their own experiences within co-op as well as the skills that were developed. Data analysis revealed the following nine themes: (a) resume-building and interview preparation were essential skills learned to aid in their co-op search; (b) the ability to “try out” various settings and areas of interest was experienced; (c) participants’ initial anxiety was gradually replaced with greater comfort and confidence; (d) participants were able to learn from positive as well as negative characteristics of their co-workers; (e) positive feedback, support, and networking opportunities were received from co-workers and clients; (f) interviewing confidence as well as increased resume-building skills were useful in obtaining a full-time job; (g) an increased sense of professionalism was gained, along with job-specific skills, and communication skills; (h) positive attitudes were experienced, along with a perceived ability to handle success and challenges in a new job; and (i) participants gained leadership and supervisory skills, enabling them to take on responsibility in their current full-time work after receiving their degree. It was determined that participating in cooperative education is beneficial to students and that the graduates still consider it an integral part of their college experience. The students also shared that they were able to use the skills and knowledge learned from their co-op in the job search as well as in their current full-time job. Therefore, it is determined that the study supports the idea that career self-efficacy is in fact developed by recent LAS graduates while participating in co-op.
Keywords: cooperative education career self-efficacy; Career; Self-efficacy; Adult Education (0516); Higher Education (0745); Higher Education Administration (0446)